2020
DOI: 10.1097/sla.0000000000004466
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Robotic Versus Laparoscopic Distal Gastrectomy for Gastric Cancer

Abstract: Objective: To evaluate the short-term outcomes of patients with GC who received RDG or LDG. Summary Background Data: Despite the increasing use of RDG in patients with GC, its safety and efficacy compared to those of LDG have not been elucidated in a randomized controlled trial. Methods: Three hundred patients with cT1-4a and N0/+ between September 2017 and January 2020 were enrolled in this randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
146
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 64 publications
7
146
1
1
Order By: Relevance
“…For RDG, Lu’s RCT study showed that patients in the RDG group reduced postoperative morbidity compared with LDG group (9.2% vs 17.6%, p=0.039). 12 As the incidence rates in the TRDG group range from 4.7% to 15.9% in retrospective studies 16 31 32 and given the proficiency of surgeons who perform robotic gastrectomy and the reasonable cost-effectiveness of robotic surgery, 9.0% is the expected 30-day postoperative morbidity in the TRDG group in this study. PASS V.15.0 software was used to calculate sample sizes of 307 with a 1:1 ratio in each group, achieving 80% power to detect a difference between the group proportions of 7.5%.…”
Section: Methods and Analysismentioning
confidence: 71%
See 1 more Smart Citation
“…For RDG, Lu’s RCT study showed that patients in the RDG group reduced postoperative morbidity compared with LDG group (9.2% vs 17.6%, p=0.039). 12 As the incidence rates in the TRDG group range from 4.7% to 15.9% in retrospective studies 16 31 32 and given the proficiency of surgeons who perform robotic gastrectomy and the reasonable cost-effectiveness of robotic surgery, 9.0% is the expected 30-day postoperative morbidity in the TRDG group in this study. PASS V.15.0 software was used to calculate sample sizes of 307 with a 1:1 ratio in each group, achieving 80% power to detect a difference between the group proportions of 7.5%.…”
Section: Methods and Analysismentioning
confidence: 71%
“…[8][9][10][11] Recently, Lu's RCT study demonstrated that RDG had lower postoperative complication rate compared with LDG for clinical stage I-III patients. 12 These results indicate the potential superiority of RDG. However, the currently available evidence on robotic gastrectomy is still limited, which need more evidence-based studies to explore the effect of RDG.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 81%
“…Robotic gastrectomy (RG) for gastric cancer (GC) was introduced speci cally to overcome the kinematic restrictions of conventional laparoscopic gastrectomy (LG), including the limited range of movement, ampli cation of operator hand tremors, and inconvenient surgical positioning. We and others have suggested that robotic approach for GC led to a reduction of the incidence of postoperative complications, resulting in improved safety and effective surgical results compared with LG [1][2][3][4] . The total operation time, however, has been reported in several studies to be longer by RG than by LG [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…We and others have suggested that robotic approach for GC led to a reduction of the incidence of postoperative complications, resulting in improved safety and effective surgical results compared with LG [1][2][3][4] . The total operation time, however, has been reported in several studies to be longer by RG than by LG [4][5][6][7] . These longer operation times might be attributed to the setting and docking of the robotic arms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, robotic gastrectomy showed reliable surgical outcomes as an alternative for laparoscopic gastrectomy in minimally invasive surgery for the treatment of gastric cancer [14][15][16][17][18][19]. However, these studies focused on singlequality indicators such as bleeding, retrieved lymph nodes, complications, and mortality to compare short-term outcomes.…”
Section: Introductionmentioning
confidence: 99%